Bentall Surgery for Aortic Root Aneurysm in a Patient with Marfan Syndrome - Maruf, Mohammad Fazle; Hossain, Nazmul; Akter, Tahmina; Chowdhury, Asif Ahsan; Hasan, Kamrul; Karim, Rezaul; Ahsan, NA Kamrul (Cardiovascular Journal, 2015)
A 34 yrs old man of marfan syndrome, visited us with the complaints of palpitation, easy fatigability and chest discomfort for last 1year. He was pointed out to have the aortic root enlargement with severe aortic regurgitation & mild mitral regurgitation by echocardiography and CT angiogram. We excised the aneurysm, implanted a composite graft with prosthetic valve conduit (Bentall operation), directly attached the coronary arteries to the aortic graft, and made the distal anastomosis to the divided aorta. Postoperative course was uneventful. To our knowledge, this is the first successful case of Bentall operation in national Institute of cardiovascular Diseases. Cardiovasc. j. 2015; 8(1): 78-81